Water Service Provision of Asha’rawea Area and the Future Collaboration with South West Area of Jenin Governora - Abdulrahman Barakat; Hothayfah Asous; Khaled Odeh (My University, 2018)
Asha’rawea area is located in the north part of Tulkarm governate in the West Bank. The total population of Asha’rawea area in 2017 was about 57,000 capita located in 14 communities. Asha’rawea area lies on the western slopes of the west bank, which are characterized by gentle slopes. Asha’rawea area is located on the west aquifer which consider the richest Palestinian aquifer by ground water. In contrast, in S-W area of Jenin a lot of villages are without adequate water supply due to no adequate fund to establish such projects and complex process to get permit from Israeli authorities. The methodology of our project will include estimating of the future population of each community and calculate the consumption of water in three sectors which are domestic, agriculture and livestock. Then, we are going to study the available water resources and discuss the expected future scenarios and suggest enhancement strategies. The main goal of project is to develop the idea of a current successful collaboration between Kafir ra’i and Illar municipalities and expand it to cover the remaining Area of Asha’rawea and S-W area of Jenin which facilitate creating regional water utility that works to share fairly the pumped water for domestic purposes. At the end of our project, we present a proper assessment of water service providers in Asha’rawea area and we found that there is a possibility to supply S-W area of Jenin to solve the problems of water scarcity by studying how much longer the surplus water in Asha’rawea Area will be sufficient to provide the needed quantity for 2017, 2022, 2027 and 2032 in S-W Area of Jenin and we discuss the idea of collaboration by create a collaboration model